26-2(2x+2)=4(x+2)+6

Simple and best practice solution for 26-2(2x+2)=4(x+2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26-2(2x+2)=4(x+2)+6 equation:


Simplifying
26 + -2(2x + 2) = 4(x + 2) + 6

Reorder the terms:
26 + -2(2 + 2x) = 4(x + 2) + 6
26 + (2 * -2 + 2x * -2) = 4(x + 2) + 6
26 + (-4 + -4x) = 4(x + 2) + 6

Combine like terms: 26 + -4 = 22
22 + -4x = 4(x + 2) + 6

Reorder the terms:
22 + -4x = 4(2 + x) + 6
22 + -4x = (2 * 4 + x * 4) + 6
22 + -4x = (8 + 4x) + 6

Reorder the terms:
22 + -4x = 8 + 6 + 4x

Combine like terms: 8 + 6 = 14
22 + -4x = 14 + 4x

Solving
22 + -4x = 14 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
22 + -4x + -4x = 14 + 4x + -4x

Combine like terms: -4x + -4x = -8x
22 + -8x = 14 + 4x + -4x

Combine like terms: 4x + -4x = 0
22 + -8x = 14 + 0
22 + -8x = 14

Add '-22' to each side of the equation.
22 + -22 + -8x = 14 + -22

Combine like terms: 22 + -22 = 0
0 + -8x = 14 + -22
-8x = 14 + -22

Combine like terms: 14 + -22 = -8
-8x = -8

Divide each side by '-8'.
x = 1

Simplifying
x = 1

See similar equations:

| 5+x=13+4 | | 7u=33-4y | | 4k-6=-2k-6-2 | | Y=arcsin(2x+5) | | -10=9(x-9) | | (m*3)+(b*2)+8=45 | | 6(x-20)=36-10x | | 13x-2(x+40)=8x+1 | | 4+x^2-15-6x=0 | | x^2+4=3(2x+5) | | 6x+6y=348 | | x-0.20=56 | | 5x-15=5x-15 | | 111=-3(5+6x) | | .25x+x=3800 | | 87=3(-3x+8) | | 4x(x+4)=9 | | 3n+5-4n=-22 | | 6x-21=33+10x | | 30x+65y=5840 | | -2(7k+9)=25 | | =95-2 | | 2(3x-10)=1 | | 4x+12x=-2254 | | -8(3+9a)=-20 | | 6(3x-10)=46 | | 5(3x-10)=46 | | 4(3x-10)=46 | | 3(3x-10)=46 | | 1(3x-10)=46 | | 12x-25=-63+7x | | 3(-2x+5)=12-4x |

Equations solver categories